Effect of IP-10/CXCR3 signaling pathway on rats with diabetic retinopathy: IP-10/CXCR3 in diabetic retinopathy - Ji, Fei; Zhang, Hongjie; Ge, Qian (Cellular and Molecular Biology, 2023)
This study aimed to investigate the effect of the interferon-inducible protein-10 (IP-10)/C-X-C motif chemokine receptor 3 (CXCR3) signaling pathway on rats with diabetic retinopathy. A total of 21 Sprague-Dawley rats were selected as the objects and divided into control (n=7), model (n=7) and inhibitor (n=7) groups. The rats in control group did not receive any treatment. The diabetic retinopathy model was established using streptozotocin and vascular endothelial growth factor in model group, while the rats in inhibitor group were treated with AMG 487, an inhibitor of the IP-10/CXCR3 signaling pathway, based on the treatment in model group. The changes in gene expression patterns in rats with diabetic retinopathy were screened by sequencing. After the differential genes were determined, the pathways mainly related to the complication were obtained via enrichment analysis. The expression of the IP-10/CXCR3 signaling pathway, the apoptotic cells and the expression of inflammatory molecules (IL-6, IL-12, TNF-α and IL-1β) in each group of rats were detected. It was shown in volcano plot that there were some differentially expressed genes (fold change >1.2, P<0.01) in retinal tissues of rats in control and model groups. Meanwhile, the heatmap displayed that there were great differences in the gene expression patterns between control and model groups, and the gene expressions of IP-10 and CXCR3 in model group were higher than those in control group (P<0.05). The differential genes in control and model groupwere enriched in such processes as the cAMP metabolic regulatory pathway, chemotaxis of immunocytes, proliferation of endothelial cells, response of cytokine receptors, apoptosis, mTOR signaling pathway and TGF-β-related signaling pathway. The mRNA expressions of IP-10 and CXCR3 in model group were higher than those in control group (P<0.05), while they were notably lower in inhibitor group than those in model group (P<0.05). Besides, the protein levels of IP-10 and CXCR3 were identical to the mRNA levels. The apoptotic cells were increased markedly in model group compared with those in control group (P<0.05) and inhibitor group (P<0.05). Model group exhibited higher expression levels of IL-6, TNF-α and IL-1β in retinal tissues than control group (P<0.05), while inhibitor group had distinctly lower expression levels of IL-6, TNF-α and IL-1β in retinal tissues than model group (P<0.05). The IP-10/CXCR3 signaling pathway can affect rats with diabetic retinopathy.